2017
DOI: 10.1007/s12291-017-0689-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical and Histopathological Grades in Oral Submucous Fibrosis Patients with Oxidative Stress Markers in Saliva

Abstract: This study aimed to correlate the oxidative stress marker levels in saliva with the clinical stage based on mouth opening, fibrotic bands and histopathological grades of oral submucous fibrosis (OSF) patients. The study included patients clinically diagnosed with OSF (n = 63) and equal number of age and gender matched controls. Patients with OSF were defined by mouth opening stage, fibrotic bands and histopathological grades. Unstimulated saliva from both control and OSF patients were analysed for oxidative ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The included studies had found a statistically significant increase in serum MDA levels in OSMF patients compared with controls (p < 0.001). 1,18,20,22,26,28,29,30,31,32,33,34,35,36,37,38 Similarly, other studies also observed a significant difference p-value <0.01 4 and p-value <0.05. 39,40 A few studies have also reported significantly higher salivary MDA levels in OSMF compared with healthy subjects (p < 0.001).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…The included studies had found a statistically significant increase in serum MDA levels in OSMF patients compared with controls (p < 0.001). 1,18,20,22,26,28,29,30,31,32,33,34,35,36,37,38 Similarly, other studies also observed a significant difference p-value <0.01 4 and p-value <0.05. 39,40 A few studies have also reported significantly higher salivary MDA levels in OSMF compared with healthy subjects (p < 0.001).…”
Section: Discussionmentioning
confidence: 72%
“…Correlation analysis of lipid peroxides levels with histological grades showed a positive correlation (p < 0.01). 36 The authors concluded that the lipid peroxidation increases with the disease severity, reflecting the extent of tissue injury. 5,20,26,30,39 Abbreviations: Hl, hemolysate; Mi, mitochondria; Pl, plasma; Sa, saliva; Se, serum; Ti, tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple biomarkers may increase OSF diagnosis specificity and sensitivity and could include 8-OHdG, MDA, vitamin C, and vitamin E [99]. In another study, total salivary protein and lipid peroxides were higher but vitamins A, C, and E and salivary SOD and GPx were lower in OSF patients than the controls [100]. Thus, oxidative stress is correlated with OSF progress.…”
Section: Biomarkers In Osf Salivamentioning
confidence: 96%